2022
DOI: 10.1038/s41522-022-00367-z
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory microbes and genes as potential biomarkers of Parkinson’s disease

Abstract: As the second-largest neurodegenerative disease in the world, Parkinson’s disease (PD) has brought a severe economic and medical burden to our society. Growing evidence in recent years suggests that the gut microbiome may influence PD, but the exact pathogenesis of PD remains unclear. In addition, the current diagnosis of PD could be inaccurate and expensive. In this study, the largest meta-analysis currently of the gut microbiome in PD was analyzed, including 2269 samples by 16S rRNA gene and 236 samples by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…Additionally, the concentration of these bacterial species correlated with the clinically observed severity of PD ( p < 0.01). Very recent Chinese research has confirmed these results [[88]], which suggests that Desulfovibrio bacteria take part in the pathogenesis of PD, which opens a new avenue for patient classification and treatment.…”
Section: Discussionmentioning
confidence: 75%
“…Additionally, the concentration of these bacterial species correlated with the clinically observed severity of PD ( p < 0.01). Very recent Chinese research has confirmed these results [[88]], which suggests that Desulfovibrio bacteria take part in the pathogenesis of PD, which opens a new avenue for patient classification and treatment.…”
Section: Discussionmentioning
confidence: 75%
“…Many studies have shown that individuals with PD have a much higher prevalence of Akkermansia and Akkermansia muciniphila than healthy participants, suggesting that Akkermansia may be associated with the pro-inflammatory state of PD [ 16 ]. Interestingly, in our study, rotenone intake markedly increased the abundance of Akkermansia , which is consistent with the results of patients with PD.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the microbiota in the gut may affect the concentrations of plasma amino acids. Emerging evidence indicates that individuals with PD suffer from unbalanced gut microbiota compositions [ 16 , 76 ], which suggests that gut microbes are implicated in the pathophysiology of PD. The brain requires BCAAs as a nitrogen source to keep the glutamate–glutamine cycle between astrocytes and neurons functioning correctly [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Growing evidence supports the idea that microbial dysbiosis, leaky gut syndrome and a proinflammatory intestinal environment are central components of the pathogenesis of PD. [4][5][6][7] The gut metabolome is essential for metabolic homeostasis but is also involved in communication between the microbiome and the subepithelial structures of the gut, which has multifold systemic implications for the organism. Short-chain fatty acids (SCFAs) are a major group of metabolites involved in the microbiome-gut interaction and are produced through the anaerobic fermentation of dietary fibers.…”
Section: Introductionmentioning
confidence: 99%